Teacher Self-Efficacy and Teacher Attitudes Toward Separation Anxiety in Early Childhood - Nur, Fatikhatun (The Future of Education Journal, 2025)
Separation anxiety experienced by young children, particularly when they begin school, has become an important concern because it can negatively affect the learning process and children’s overall development. This paper aims to examine the relationship between teacher self-efficacy and teacher attitudes toward separation anxiety in early childhood students. Using Albert Bandura’s social cognitive theory, self-efficacy is defined as an individual’s belief in their ability to handle situations and achieve positive outcomes. In the context of early childhood educators, self-efficacy refers to teachers’ beliefs in their capacity to influence young children’s learning and development. The findings indicate that teachers with high self-efficacy tend to demonstrate more positive and constructive attitudes in addressing students with separation anxiety, leading to positive developmental outcomes for children. Four factors influencing teacher self-efficacy mastery experiences, social modeling, social persuasion, and physical and emotional states are also discussed to understand how self-efficacy can be cultivated and strengthened. Positive teacher attitudes toward children with separation anxiety, including empathy, patience, affection, and consistent support, help children feel safe and comfortable when separating from their attachment figures in the school environment.